The Cultural Values of Siri' in Bugis Community Represented in Tarung Sarung Film (2020) - Mundi Rahayu; Maulidiyah Nur Cholisa Hafshah; Ihwanarotama Bella Indriasandi (Pioneer: Journal of Language and Literature, 2023)
Film Tarung Sarung (2020) presents the narration of young people’s adventure with the setting of local culture of Bugis community, which emphasizes the value of siri' culture. Local culture in contemporary films is still rarely discussed in depth. Thus, this study aims to answer the gap of study. This study explicitly discusses the cultural value of siri', represented in Tarung Sarung film. The aim of this research is to get understanding on cultural values of siri' in Bugis community represented in film Tarung Sarung. The method used in this research is qualitative-descriptive with a film studies approach. This study uses Stuart Hall's representation theory to determine the representation of siri' cultural values. Siri' cultural values in this film are represented as inspiration to move the characters in solving problems. There are two points obtained in this study. The first is siri' culture is very prominent, especially in the relationship between men and women. The second, siri' culture is represented as an important ideology to uphold self-respect among the Bugis community.